Rancang Bangun Alat Ukur Torsi dan Putaran Untuk Pengujian Turbin Savonius Pada Wind Tunnel Berbasis mikrokontroler - Ruzita sumiati; Uyung Gatot S. Dinata; Dendi Adi Saputra; Riswan Riswan; Fahri Triharyono; Rahil Abde Andika; Fharel Abdillah (Jurnal Teknik Mesin, 2024)
The objective of this research is to design and develop a torque measurement device using a braking system and a rotational speed measurement tool for a Savonius turbine shaft, applied in a wind tunnel, with data acquisition controlled by an Arduino Uno microcontroller. The methodology employed in this research is the design and build method. The testing results indicate that the torque measurement device controlled by the Arduino Uno functions effectively. Comparing the results of braking force measurements using manual methods and data acquisition revealed a 2, 231 % error. Additionally, the rotational speed measurements using a tachometer and those using an encoder controlled by the Arduino Uno showed a small error of 0,59 %. Data were continuously monitored on a laptop screen during testing. Thus, this device can be utilized as an auxiliary measurement tool to assess the performance of a Savonius turbine